2014
DOI: 10.1002/hbm.22478
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of morphometric variability of subthalamic nucleus, red nucleus, and substantia nigra in advanced Parkinson's disease patients using automatic segmentation and PCA‐based analysis

Abstract: Subthalamic nucleus (STN) deep brain stimulation (DBS) is an effective surgical therapy to treat Parkinson's disease (PD). Conventional methods employ standard atlas coordinates to target the STN, which, along with the adjacent red nucleus (RN) and substantia nigra (SN), are not well visualized on conventional T1w MRIs. However, the positions and sizes of the nuclei may be more variable than the standard atlas, thus making the pre-surgical plans inaccurate. We investigated the morphometric variability of the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 51 publications
1
39
1
Order By: Relevance
“…We further identified [as in previous work, see, for instance, Xiao et al (2014)] midbrain nuclei, as the SN, the RN, and also, in the diencephalon, the STh (Fig. 5), by inspection of hypo-intense areas in T2-weighted images (see also Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We further identified [as in previous work, see, for instance, Xiao et al (2014)] midbrain nuclei, as the SN, the RN, and also, in the diencephalon, the STh (Fig. 5), by inspection of hypo-intense areas in T2-weighted images (see also Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…‰ homeostasis, sensory-motor functions, sleep and wakefulness cycles, defensive behaviors, and nociception , visualization of Bn in vivo by structural MRI has shown slower progress compared with imaging of other brain areas. Indeed, except for a few midbrain nuclei (e.g., the SN and RN) and the STh (Chowdhury et al, 2013;Keuken et al, 2014;Kwon et al, 2012;Menke et al, 2010;Xiao et al, 2014), the lower relaxivity-based MRI contrast of Bn compared with the cortex (see for instance Fig. 1) has been a barrier to the in vivo structural identification of most Bn and hindered investigation of their functional and structural connections.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In conventional DBS planning procedures, the location of the STN is determined either by scaling standard brain atlases [17,18] to fit the patient's anatomy as seen in the pre-operative T1w MRI or by inferring the position of the STN relative to landmarks such as anterior and posterior commissure points. However, some studies [19][20][21] have shown that high anatomical variability exists for the STN and consequently simple atlas-fitting cannot sufficiently capture the large variance in the location, size and orientation of the nucleus. More recent indirect methods employ either hierarchical affine [22] or nonlinear registration [23] to deform digitized atlases to improve anatomical alignment, and lend automation to structural identification.…”
Section: Introductionmentioning
confidence: 98%